Effects of Zinc Alpha2 Glycoprotein on Lipid Metabolism of Liver in High-Fat Diet-Induced Obese Mice - Fan, Guoqiang; Qiao, Yu; Gao, Shixing; Guo, Jun; Zhao, Ruqian; Yang, Xiaojing (Hormone and Metabolic Research, 2017)
Zinc alpha2 glycoprotein (ZAG) is a new type of adipokine involved in adipose tissue mobilization, however, little is known about its lipid metabolism effect in liver. Therefore, we investigated the effects of ZAG in the regulation of hepatic lipid accumulation. Mice were randomly divided into two groups; one was fed a normal diet and another was fed a high-fat diet for eight weeks to establish obesity model. After that, the normal diet group was divided into ND (injection of pcDNA3.1) and NDZ (injection of ZAG recombinant plasmid) and the high-fat diet group was divided into HF (injection of pcDNA3.1) and HFZ (injection of ZAG recombinant plasmid). The mice were weighed once per week and injected with plasmid once every three days for eight times. The results showed that body weight and hepatic TG content were decreased dramatically in HFZ group compared with HF group. The stearoyl-CoAdesaturase1 (SCD1) and Acyl-CoA Synthetase-1 (ACSS1) protein levels in HFZ group were significantly decreased. Furthermore, phosphorylated hormone sensitive lipase (P-HSL) was significantly higher in HFZ group. In HFZ group, hepatic fatty acid translocase (CD36) and fatty acids binding protein-1 (FABP1) protein levels were reduced. In addition, the expression of phosphorylated protein kinase A (PPKA) in HFZ group was higher than the HF group. Meanwhile, NDZ group showed significantly decreased body weight and increased P-HSL level though the hepatic TG content showed no significantly changes compared with the ND group. Therefore, we conclude that ZAG may be beneficial for preventing high-fat-diet-induced hepatic lipid metabolic disorders.
Keywords: zinc alpha2 glycoprotein; lipid metabolism; mouse; liver